Mathematical Problem-Solving Abilities of Students in Solving Algebra Problems: A Quantitative Study on Junior High School Students - Ovan, Ovan; Sirate, Sitti Fatimah Sangkala; Mulyati, Mulyati; Ramadhana, Risky; Hadi, Abdul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study investigates the algebra problem-solving abilities of junior high school students and explores the factors influencing their performance. Using a quantitative research design, the study assesses students' problem-solving skills through an algebra test and surveys measuring metacognitive awareness and self-confidence. A sample of 62 junior high school students was selected using stratified random sampling. The results show that while students demonstrated moderate proficiency in algebra, they particularly struggled with word problems, which require translating real-world scenarios into algebraic expressions. Performance on word problems was notably lower than on tasks involving basic algebraic manipulations. The study also reveals significant correlations between students’ metacognitive awareness and self-confidence and their problem-solving abilities, suggesting that students who are more aware of their thinking processes and confident in their abilities tend to perform better. The findings underscore the importance of metacognitive skills and self-confidence in improving algebra problem-solving and suggest that instructional strategies focusing on these aspects could enhance students' mathematical performance. This study has important implications for algebra instruction, recommending the incorporation of metacognitive strategies, reflective thinking, and problem-solving frameworks into the curriculum. Future research should explore the impact of different teaching methods and longitudinally track students' problem-solving development